Visual Outcome and Complications in Retro-Pupillary Iris Claw Intra-Ocular Lens in Patients with Insufficient Capsular/Zonular Support: Doi: 10.36351/pjo.v41i2.1853 - Ahmad, Imran; Gul, Nazli; Bilal Khan; Jawad hamayun; Fahad khan (Pakistan Journal of Ophthalmology, 2025)
Purpose: To determine the safety and effectiveness of iris claw lenses in cases of deficient capsular support. Study Design: Interventional case series. Place and Duration of Study: Khyber Teaching Hospital, from June 2023 to April 2024. Methods: Aphakic patients with posterior capsule rupture and insufficient support for sulcus fixation intraocular lens (IOL) implantation were included in the study. Exclusion criteria included patients with atrophic iris or deficient iris for holding iris claw IOL, dilated pupils due to poor function of the constrictor pupillae muscle, pre-operative corneal scars, diabetic retinopathy, or posterior segment pathologies. Retro-pupillary placement of iris claw IOL was performed in all cases. Postoperatively, corneal sutures were removed 40 days after surgery, and visual acuity was assessed one week after suture removal. For quantitative variables, mean and standard deviation were calculated, while frequencies were used for qualitative variables. Pre- and post-operative best-corrected visual acuity (BCVA) were compared. A p-value of less than 0.05 was considered statistically significant. Results: A total of 35 iris claw procedures were performed. The mean age of participants was 60.31±6.90 years, with 54.28% male and 45.72% female patients. No complications were documented in 74.28% of patients. Documented complications included: irregular iris (12.24%), High intraocular pressure (2.85%), IOL subluxation (2.85%), Cystoid macular edema (2.85%) and Hyphema (2.85%). Conclusion: The study demonstrates that retro-pupillary placement of the iris claw IOL is a safe and effective procedure for patients with deficient capsular support, with a majority experiencing no postoperative complications.